2010
DOI: 10.1021/nl101773c
|View full text |Cite
|
Sign up to set email alerts
|

A DNA−Silver Nanocluster Probe That Fluoresces upon Hybridization

Abstract: DNA-templated silver nanoclusters (DNA/Ag NCs) are an emerging set of fluorophores that are smaller than semiconductor quantum dots and can have better photostability and brightness than commonly used organic dyes. Here we find the red fluorescence of DNA/Ag NCs can be enhanced 500-fold when placed in proximity to guanine-rich DNA sequences. On the basis of this new phenomenon, we have designed a DNA detection probe (NanoCluster Beacon, NCB) that "lights up" upon target binding. Since NCBs do not rely on Forst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
600
4
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(617 citation statements)
references
References 35 publications
(73 reference statements)
7
600
4
2
Order By: Relevance
“…2,8,9,14,15 Recent studies have shown that luminescent Au and Ag NCs are promising optical probes for bioimaging and biosensing applications. 4,[16][17][18][19][20] This finding has led to the development of various methods for the synthesis of highly luminescent Au and Ag NCs. 2, 21 On the other hand, insofar as nanostructured Ag-based materials are concerned, they are finding an increasing usage for antimicrobial applications owing to the unique chemistry of Ag interfacing with microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…2,8,9,14,15 Recent studies have shown that luminescent Au and Ag NCs are promising optical probes for bioimaging and biosensing applications. 4,[16][17][18][19][20] This finding has led to the development of various methods for the synthesis of highly luminescent Au and Ag NCs. 2, 21 On the other hand, insofar as nanostructured Ag-based materials are concerned, they are finding an increasing usage for antimicrobial applications owing to the unique chemistry of Ag interfacing with microorganisms.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25] Amongst these stabilizers, DNA is very attractive due to its excellent programmability, stability and cost-effectiveness. [26][27][28][29][30] Taking advantage of the strong binding interaction between cytosine and Ag + , a wide range of emission colors are obtained by using various cytosine-rich DNA sequences, [12][13][14][15][16][17]31,32 where NaBH4 has been the exclusively used reducing agent.…”
Section: Introductionmentioning
confidence: 99%
“…[19][20][21][22][23] On the practical side, by rational incorporation of DNA aptamers, the fluorescence signaling of AgNCs has been successfully coupled with the molecular recognition property of DNA to design biosensors and smart imaging probes. [24][25][26][27][28][29][30][31][32][33][34][35][36] An interesting and useful discovery is that the fluorescence of many NCs is strongly quenched by Hg 2+ , allowing its detection at low nM and even sub-nM concentrations. 20,[37][38][39][40][41][42] Despite its importance in analytical chemistry, our fundamental understanding of NCs is still quite limited.…”
Section: Introductionmentioning
confidence: 99%